2013
DOI: 10.5433/1679-0359.2013v34n1p57
|View full text |Cite
|
Sign up to set email alerts
|

Fontes de fósforo associadas à inoculação com Pseudomonas fluorescens no desenvolvimento e produtividade do milho

Abstract: ResumoA utilização crescente de fertilizantes para elevar a disponibilidade de P para as plantas tem promovido um forte impacto econômico no setor agrícola. Visando a melhor eficiência do uso dos fertilizantes fosfatados, este estudo teve como objetivo avaliar o efeito de fontes de P associados à inoculação com Pseudomonas fluorescens via sementes, no desenvolvimento e nos componentes de produção de plantas de milho. O experimento foi conduzido a campo, em esquema fatorial 6x2, em blocos casualizados, com quat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…In addition, some isolates of the genera can suppress phytopathogens LUDWIG et al, 2009) by producing secondary metabolites, such as siderophores and antibiotics (BOTELHO; MENDONÇA-HAGLER, 2006;VOYARD et al, 1994;LOPER, 1991). Several reports of the plant development improvement, such as corn, beans, cotton, soybeans and rice inoculated with isolates from genera Bacillus and fluorescent Pseudomonas are described (FERREIRA; KNUPP; MARTIN-DIDONET, 2014;CHAVES;ZUCARELI;JUNIOR, 2013;SILVA, 2013;ASSUNPÇÃO et al, 2009;ARAUJO, 2008;LAZZARETI MELO, 2005;ARAÚJO;HUNGRIA, 1999). These reports emphasize the potential use of these rhizobacteria to a larger spectrum of plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some isolates of the genera can suppress phytopathogens LUDWIG et al, 2009) by producing secondary metabolites, such as siderophores and antibiotics (BOTELHO; MENDONÇA-HAGLER, 2006;VOYARD et al, 1994;LOPER, 1991). Several reports of the plant development improvement, such as corn, beans, cotton, soybeans and rice inoculated with isolates from genera Bacillus and fluorescent Pseudomonas are described (FERREIRA; KNUPP; MARTIN-DIDONET, 2014;CHAVES;ZUCARELI;JUNIOR, 2013;SILVA, 2013;ASSUNPÇÃO et al, 2009;ARAUJO, 2008;LAZZARETI MELO, 2005;ARAÚJO;HUNGRIA, 1999). These reports emphasize the potential use of these rhizobacteria to a larger spectrum of plants.…”
Section: Introductionmentioning
confidence: 99%
“…(W6), Bacillus megaterium (W19) and Bacillus cereus (UFV40) increased by 48, 46 and 45 % the production of bulbs per hectare, respectively, when compared to the control, which received standard crop fertilization. Chaves et al (2013) observed that P. fluorescens inoculation on corn produced 87 % of relative agronomic efficiency, when comparing TSP fertilization and control without P.…”
Section: Resultsmentioning
confidence: 95%
“…Estudos têm apontado para o potencial de solubilização de fosfatos por BPCV dos gêneros Pseudomonas e Bacillus, bem como por alguns fungos associativos como é o caso das Micorrizas, Aspergillus, etc. (SOUCHIE et al, 2005;CHAVES et al, 2013;SOUSA et al, 2016).…”
Section: Introductionunclassified